Instructions for Authors - Cock, I.E. (Pharmacognosy Communications)
Pharmacognosy Communications (www.phcogcommn.org) is a new journal published by Pharmacognosy Network Worldwide (www.phcog.net). It is a peer reviewed journal aiming to publish high quality original research articles, methods, techniques and evaluation reports, critical reviews, short communications, commentaries and editorials of all aspects of Pharmacognosy and medicinal plant research. The journal is aimed at a broad readership, publishing articles on all aspects of pharmacognosy, and related fields. The journal aims to increase understanding of pharmacognosy as well as to direct and foster further research through the dissemination of scientific information by the publication of quality manuscripts. The submission of original contributions in all areas of pharmacognosy are welcomed.